2012
DOI: 10.1007/s11409-012-9088-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards efficient measurement of metacognition in mathematical problem solving

Abstract: Metacognitive monitoring and regulation play an essential role in mathematical problem solving. Therefore, it is important for researchers and practitioners to assess students' metacognition. One proven valid, but time consuming, method to assess metacognition is by using think-aloud protocols. Although valuable, practical drawbacks of this method necessitate a search for more convenient measurement instruments. Less valid methods that are easy to use are self-report questionnaires on metacognitive activities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 55 publications
1
92
0
7
Order By: Relevance
“…Given that deep cognitive and metacognitive strategies were positive predictors of students' problem solving achievement, it is imperative to design learning environments that reduce boredom or that can provide scaffolds for students when boredom arises to shift their learning strategies or regulate that boredom. As previous research in mathematics problem solving has shown, central to successful problem solving is employment of these kinds of deep cognitive and metacognitive strategies (Jacobse & Harskamp, 2012;Muis, 2008;Schoenfeld, 1985). Our results provide support for this.…”
Section: Consequencessupporting
confidence: 84%
See 1 more Smart Citation
“…Given that deep cognitive and metacognitive strategies were positive predictors of students' problem solving achievement, it is imperative to design learning environments that reduce boredom or that can provide scaffolds for students when boredom arises to shift their learning strategies or regulate that boredom. As previous research in mathematics problem solving has shown, central to successful problem solving is employment of these kinds of deep cognitive and metacognitive strategies (Jacobse & Harskamp, 2012;Muis, 2008;Schoenfeld, 1985). Our results provide support for this.…”
Section: Consequencessupporting
confidence: 84%
“…In this situation, the individual is more likely to be vigilant while solving the problem, ensuring to understand the problem and its various components, generating relevant prior knowledge, coordinating informational sources, making comparisons, and generating inferences, which are considered deep processing strategies. The individual is also more likely to continually evaluate progress, and check answers against set goals, which are key metacognitive processes for successful problem solving (Jacobse & Harskamp, 2012). The importance placed on correctly solving the problem may also result in anxiety if issues arise when solving the problem, confusion or frustration if the issue cannot be resolved, or enjoyment if there is resolution.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…Therefore, lack of paraphrasing indicates that students omit this important stage. It was also observed in Jacobse and Harskamp's (2012) study that students did not use paraphrasing during mathematical problem solving while thinking aloud. One of the reasons for this is tendency to solve the problems as quickly as possible, probably due to pressure of succeeding in national exams; hence it may not be very surprising that all groups skipped this part quickly.…”
Section: Discussionmentioning
confidence: 85%
“…The subject is encouraged to give a concurrent account of their thoughts and avoid interpretation or explanation of what they are doing; they only have to concentrate on the task (Ericsson & Simon, 1993;Someren, Bardnard, & Sandberg, 1994). One of the major advantages of using the think-aloud method is being able to capture the individual's immediate thoughts (Ericsson & Simon, 1993;Jacobse & Harskamp, 2012;Wade, 1990;Young, 2005), which is important in understanding students' problem solving processes. The thinkaloud method is considered a valid form of verbal data collection (Ericsson, 2006;Ericsson & Simon, 1993) and researchers in the field of social sciences have been using this method for quite some time.…”
mentioning
confidence: 99%
“…Think-aloud Protocols: Think aloud protocols are on-line measuring techniques which ask individuals tell-describe their thoughts verbally while they are working on a task (problem) [3,48]. Think-aloud protocols provide the richest data which can be obtained about metacognitive processes throughout learning, as they are related to gathered metacognitive behaviours [3] during a learning task [52].…”
Section: Data Collection Instruments and Data Collectionmentioning
confidence: 99%